2013
DOI: 10.1111/1574-6941.12067
|View full text |Cite
|
Sign up to set email alerts
|

Faecal microbiota in lean and obese dogs

Abstract: Previous work has shown obesity to be associated with changes in intestinal microbiota. While obesity is common in dogs, limited information is available about the role of the intestinal microbiota. The aim of this study was to investigate whether alterations in the intestinal microbiota may be associated with canine obesity. Using 16S rRNA gene pyrosequencing and quantitative real-time PCR, we evaluated the composition of the faecal microbiota in 22 lean and 21 obese pet dogs, as well as in five research dogs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

21
130
4
15

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 114 publications
(170 citation statements)
references
References 51 publications
21
130
4
15
Order By: Relevance
“…Obesity was induced by ad libitum feeding for 6 months, and the same commercially available food was used in both groups. Handl et al18 used the same feeding strategy and observed that obese dogs contained increased proportions of the major bacterial phylum (>90% Firmicutes, approximately 2% of Bacteroidetes and Actinobacteria, respectively, and no significant differences were observed in the microbial communities of the ad libitum fed and restricted‐diet group, except the order Clostridiales 16. Our results showed significant differences in the microbial communities in the lean and obese groups.…”
Section: Discussionsupporting
confidence: 53%
See 4 more Smart Citations
“…Obesity was induced by ad libitum feeding for 6 months, and the same commercially available food was used in both groups. Handl et al18 used the same feeding strategy and observed that obese dogs contained increased proportions of the major bacterial phylum (>90% Firmicutes, approximately 2% of Bacteroidetes and Actinobacteria, respectively, and no significant differences were observed in the microbial communities of the ad libitum fed and restricted‐diet group, except the order Clostridiales 16. Our results showed significant differences in the microbial communities in the lean and obese groups.…”
Section: Discussionsupporting
confidence: 53%
“…The phylum Firmicutes (85.2%) was the most dominant group, but Actinobacteria (7.94%) were more abundant than Bacteroidetes (2.34%) in the lean group. In a canine obesity model study,18 Firmicutes, Fusobacteria, and Actinobacteria were the predominant bacterial phyla. The phylum Actinobacteria and the genus Roseburia were significantly more abundant in obese pet dogs.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations